1998
DOI: 10.1086/305633
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Intrinsic Shapes of Two Different Types of Dwarf Galaxies: Blue Compact Dwarfs and Dwarf Ellipticals

Abstract: We measure the apparent shapes for a sample of 62 blue compact dwarf galaxies (BCDs), and compare them with the apparent shapes for a sample of 80 dwarf elliptical galaxies (dEs). The BCDs are flatter, on average, than the dEs, but the difference is only marginally significant. We then use both non-parametric and parametric techniques to determine possible distributions of intrinsic shapes for the BCDs. The hypothesis that BCDs are oblate spheroids can be ruled out with a high confidence level (> 99%), but the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…The axis ratios of the LSB-components have a mean value and standard deviation of b/a LSB = 0.62 ± 0.18, compatible with the mean value of BCDs from Sung et al (1998) . Left: colour−magnitude diagram of the LSB-components of our primary BCD sample, compared to the Virgo early-type dwarf galaxies (labelled "dE" but including dS0s), for which colours were derived within 2R eff .…”
Section: Apparent Axis Ratio Of the Lsb-componentsupporting
confidence: 66%
“…The axis ratios of the LSB-components have a mean value and standard deviation of b/a LSB = 0.62 ± 0.18, compatible with the mean value of BCDs from Sung et al (1998) . Left: colour−magnitude diagram of the LSB-components of our primary BCD sample, compared to the Virgo early-type dwarf galaxies (labelled "dE" but including dS0s), for which colours were derived within 2R eff .…”
Section: Apparent Axis Ratio Of the Lsb-componentsupporting
confidence: 66%
“…Recent studies show that at least 70% of BCDs are mergers or interactions (Sung 2000, Pustilnik et al 2001, Bekki 2008. But however, until now, only few BCDs are known as post-mergers; He 2-10 ( Kobulnicky et al 1995), Mrk 996 (Thuan et al 1996), and Tololo 3 (Sung et al 2002). Mrk 49 has similar observational characteristics to He 2-10.…”
Section: Discussion and Summary (A) General Morphology And Comparmentioning
confidence: 99%
“…This implies that, in general, BCDs are rather old objects, and their evolution on the Hubble time scale can effectively be determined by short, but very intense star formations. On the other hand, many observations and theoretical works have recently suggested that the origin of BCDs can be closely associated with galaxy merging between low-mass dwarfs or tidal interactions (Noeske et al 2001,Östlin et al 2001, Sung et al 2002, Bekki 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations